Estructura sintáctica de las construcciones con verbos parasintéticos de los tipos a-…-ar y en-…-ar - Martínez Vera, Gabriel (2016)
I postulate an unitary syntactic structure for constructions with a-…-ar and en-…-ar parasynthetic verbs through four hypothesis: both patterns have a common basic syntactic structure regarding vP and VP, whose heads are CAUSE and BECOME,  respectively; the difference between the patterns lies on, within a scale of affectedness (Beavers 2011), the fact that a-…-ar assigns (compositionally) a result state to the theme, while this does not happen with en-…-ar. I claim that affectedness is a binary operator located higher than vP that quantizes the event determining the specificity of the result state for the object; and the morphological form of the operator is a- (if its value is positive) or en- (if its value is negative).